Ser professor de Educação Física: um sonho que se tornou realidade - Rui José Fernandes Machado Silvério (2022)
The school placement report emerged within the scope of the practicum unit, of the 2nd year of the Master's in Physical Education Teaching in Basic and Secondary Education. The school placement was carried out at a primary and secondary school in Gaia, during the academic year of 2020/2021, with the objective of graduating intern students as Masters of the Faculty of Sports of the University of Porto (FADEUP). This report demonstrates all the main experiences during the practicum year, which turned out to be an atypical year due to COVID-19. A cooperating teacher, from the school, accompanied the school placement and a supervisor teacher, from the university, as well as a group of preservice teachers. The main challenge of the school placement was the growth and development as a teaching professional of sports practice. With little experience at this level, I went through several stages throughout the school year. I grew as a professional and as a person as well. In addition to the daily challenges and constant professional overcoming, always wanting to do my best for the students, I always tried to be determined to make them better people both at school and in their integration with society. During moments of struggle with teaching. I always tried to overcome them by researching or dialoguing within the internship nucleus, at other times I felt discomfort when traveling to school because they were very exhausting with hours of waiting and exchanges between transports. However, the biggest challenge came at the end of the 1st period, where I started to live alone, after the death of my father with COVID-19 and having to manage my family responsibilities without losing sight of the objective of finishing the school placement giving my best. This study was carried out in the resident class as a result of the observation of some behavioral changes for distance learning. In order to understand the reason for the paradigm shift, which resulted in more positive behaviors, a questionnaire was prepared that was applied at the school, where the school placement was being carried out, in order to understand whether the changes had been just an isolated case if it was replicated in the students at the school in general. The results indicate that students prefer and feel more motivated with face-to-face teaching, particularly in physical education, and this fact is more evident in primary school students than secondary school students. Another evidence is that students refer to the type of contact between the participants and the classroom spaces as the biggest differences between the two types of teaching of physical education. It was also found that what students enjoyed most about distance learning is being able to stay at home and not having to go to school. A curious fact is that students who preferred distance learning feel more participatory, organized, and say they can be more attentive in classes in general.